Pengaruh Kepemimpinan Transformasional, Komitmen Organisasi, Dan Persepsi Terhadap Perubahan Terhadap Keberhasilan Implementasi Budaya Organisasi - Zulfikar PD, Moch. Iqbal; Sutisna, Deden (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to analyze the influence of transformational leadership, organizational culture, and organizational commitment on employee performance across various types of organizations. A qualitative approach with a literature review method was used to explore the relationships between these three variables based on relevant academic sources. The results show that transformational leadership plays a key role in enhancing employee performance through motivation, empowerment, and personal development, while a strong and supportive organizational culture amplifies the effect of leadership on performance. Additionally, high organizational commitment, whether affective, calculative, or normative, has a significant positive impact on both individual and organizational performance. The interaction among these three factors demonstrates that achieving optimal performance depends not only on one factor but on the harmonious integration of effective leadership, supportive culture, and strong employee commitment. This study provides insights for managers and organizational leaders to design strategies that improve performance through the development of leadership, culture, and commitment.